2019
DOI: 10.3390/microorganisms7050129
|View full text |Cite
|
Sign up to set email alerts
|

Response of Microbial Communities and Their Metabolic Functions to Drying–Rewetting Stress in a Temperate Forest Soil

Abstract: Global climate change is predicted to alter drought–precipitation patterns, which will likely affect soil microbial communities and their functions, ultimately shifting microbially-mediated biogeochemical cycles. The present study aims to investigate the simultaneous variation of microbial community compositions and functions in response to drought and following rewetting events, using a soil metaproteomics approach. For this, an established field experiment located in an Austrian forest with two levels (moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 62 publications
0
24
1
1
Order By: Relevance
“…In the literature, the effects of DRW on DOC and TDN soil concentrations and their potential leaching from the ecosystem are not clear. Previous studies have found an increase in DOC and TDN with DRW cycles 15,46 , no effect 8,46 , or a short-term change but no net effect 47,48 . This discrepancy appears linked to soil type, habitat, and/or drought frequency 15,46 and intensity 44 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In the literature, the effects of DRW on DOC and TDN soil concentrations and their potential leaching from the ecosystem are not clear. Previous studies have found an increase in DOC and TDN with DRW cycles 15,46 , no effect 8,46 , or a short-term change but no net effect 47,48 . This discrepancy appears linked to soil type, habitat, and/or drought frequency 15,46 and intensity 44 .…”
Section: Discussionmentioning
confidence: 76%
“…Aerobic respiration seven days following rewetting was much higher than control values, but this was less pronounced in the second cycle. This, along with the stronger aerobic respiration decline following the second drought, could indicate the microbial mortality and/or a shift in the microbial community composition or physiological strategies 8 to stress-avoidance through declined activity during stress 9 . Since denitrification rates returned to pre-stress levels after rewetting, there was no indication of a loss in the denitrification taxa group during drought, instead the microorganisms appear tolerant to very low soil water potential through decreased activity or accumulation of protective molecules 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial communities of soils dominate biogeochemical cycling, while playing key roles in natural ecosystems [1][2][3][4]. Soil microorganisms provide the impetus for the transformation and recycling of soil resident organic matter and elemental nutrients, such as C and N [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To stimulate biodegradation at contaminated sites, N and P amounts required are typically estimated as C/N/P ratios. Additionally, the concentration of oxygen (Abbasian et al, 2015;CCME, 2010;Meckenstock et al, 2016;Widdel & Rabus, 2001) and the availability of water for microbial growth and metabolism (Engelhardt et al, 2018;Liu et al, 2019) have been identified as predominant factors influencing biodegradation rates of PHC in the environment. Although bioremediation is a common means of treating PHC-contaminated soils, this approach has not been well demonstrated in contaminated soils from mining sites that include mine wastes and residues, despite the fact that the use of diesel as a major energy source at mining sites generally results in PHC contamination via accidental release due to equipment malfunction, maintenance, leaks, or fuel transfer spills.…”
Section: Introductionmentioning
confidence: 99%